Haronal, Peningkatan Motivasi Belajar Siswa Dengan Penerapan Latihan Terbimbing Disertai Dengan Sistem Point Pada Mata Pelajaran Ekonomi - Haronal, Haronal (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2017)
Increasing the activity of students in learning, needs teachers' creativity in selecting and implementing methods or appropriate instructional strategies. To solve the aforementioned problems, the activities of students to be more active can be fished by providing training under the guidance of teachers and provide value bonus points to students who are active in the learning takes place, such as actively ask, issue a pen-able, and is active in answering the questions given the teacher. The object of this study was the students of class XI IPS in SMA consisting of 22 students male and 8 female learners. Data analysis using quantitative analysis to analyze the motivate the students in preparing the working paper. The active level of students in the first cycle increased by 23.33% and the second cycle increased by 66.67% so the use of guided training methods and scoring bonus points can increase student motivation in learning in the classroom.